SOCIAL PROTECTION FOR SOCIAL WELFARE SERVICE RECIPIENTS (PPKS) THROUGH SIMASOS MEDIA RECORDING BY THE SOCIAL SERVICES DEPARTMENT OF KUTAI KARTANEGARA REGENCY, EAST KALIMANTAN PROVINCE - Wasistiyana, Alvita Kumara; Eviany, Eva (Jurnal Tatapamong, 2024)
Social protection efforts are one of the main supporting factors for a successful social welfare development. Therefore, data on social welfare service needees must be updated continuously and the appropriate services can be provided immediately. However, Kutai Kartanegara Regency experienced obstacles in the process of updating the data, hence the SIMASOS was created. The purpose of this research is to describe and analyze social protection through SIMASOS Media from the Social Service in Kutai Kartanegara Regency, East Kalimantan Province, as well as the supporting and inhibiting factors. This research was conducted using a descriptive qualitative method based on the theory by Sabates-Wheeler and Devereux, which examined social protection in four indicators. Social protection through SIMASOS Media data collection was implemented by fulfilling the indicators of protective, preventive, promotive, and transformative dimensions. However, one of the indicators, namely transformative, was not implemented properly due to the lack of policy follow-up on reports received through the SIMASOS media. Social protection focuses on the implementation of programs created by the government, but innovation is also needed so that the goal of a prosperous country can be achieved. One of which is through Social Welfare Service Recipients (PPKS) data collection using SIMASOS media which is based on four dimensions by Sabates and Wheeler. It was found that the supporting factors for the research object were the availability of a legal basis and the selection of the right application, while the inhibiting factors were the lack of socialization of SIMASOS media to the people of Kutai Kartanegara Regency, as well as the lack of manpower and quality of human resources responsible for the media at the Kutai Kartanegara Regency Social Service. Keywords: SIMASOS Media, PPKS, Social Protection